PELATIHAN TEKNIK DAN STRATEGI PEMASARAN PRODUK OLAHAN PEPAYA BAGI KELOMPOK PETANI BANYUMULI - Iriani, Farida; Winarti, Agus; Utama, Raden Duhita Diantiparamudita; Arifin, Miko Syahputra; Nurjaman, Jamjam (LPPM UNINUS, 2025)
Training on marketing techniques and strategies for processed papaya products, and distribution of processed products has been provided to the Banyumuli farmer group in Bojong Village, Banjarwangi District, Garut Regency, West Java Province. Road access constraints from the producer's location to the market, both to the district capital market and/or provincial capital, are an obstacle to the low income earned by this farmer group. Due to the long travel time, fresh papaya fruit quickly wilts and rots during the journey, thus lowering the selling price. Training on making formulas for processed papaya fruit products in the form of jam, syrup, and jelly candy has been carried out, then the training was continued with techniques and strategies for marketing these processed products. One of the priority problems faced is the aspect of human resource management and distribution strategies for processed products for short, medium and long distances. The method used was qualitative research with a case study approach in a Banyumuli farmer group whose main business is papaya. Data collection techniques included documentation, focus group discussions (FGDs), observation, and interviews. The training objectives are (1) to provide direction for selecting additional group members as production staff, (2) to provide training in making processed product formulas, and (3) to determine marketing techniques and strategies for processed products. The training results showed that participants were motivated to become group members, had the skills to create processed papaya product formulas, and were able to apply marketing techniques and strategies for these processed products.